1976
DOI: 10.1071/bi9760375
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Dysgenesis in Drosophila Melanogaster: A Possible Explanation in Terms of Spatial Organization of Chromosomes

Abstract: Male.recombination and female sterility, two aspects of hybrid dysgenesis in D. melanogaster, have been studied in crosses between a locally collected wild population and laboratory strains. Dysgenesis occurs in the Fl hybrid of such crosses only if the wild type is used as maie parent and the laboratory strain as female, suggesting an interaction between genotype and cytoplasm. However the results from further crosses are difficult to interpret in terms of a conventional genotype--cytoplasm model, and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Reactive and neutral strains thus seem to result from genetic changes which occur most readily in small isolates maintained in laboratory conditions . In connection with this, it may be noted that several authors (Rosenfeld et al, 1971;Sved, 1976;Kearsey et al, 1977;Kidwell et al, 1977) have reported cases of female sterility which seem to bear some similarity to our observations.…”
Section: Introductionsupporting
confidence: 61%
“…Reactive and neutral strains thus seem to result from genetic changes which occur most readily in small isolates maintained in laboratory conditions . In connection with this, it may be noted that several authors (Rosenfeld et al, 1971;Sved, 1976;Kearsey et al, 1977;Kidwell et al, 1977) have reported cases of female sterility which seem to bear some similarity to our observations.…”
Section: Introductionsupporting
confidence: 61%
“…Some authors have suggested that the configurations of chromosomes within the interphase nucleus are under specific genetic control (41,42). In a direct approach to these problems, we have been analyzing chromosome folding patterns with the aid of intradistance plots (27,36).…”
Section: Chromosomes Assume a Wide Variety Of Configurationsmentioning
confidence: 99%
“…The term "hybrid dysgenesis" has been proposed to refer collectively to this syndrome of abnormalities (Sved, 1976).…”
Section: Introductionmentioning
confidence: 99%